EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON PLANT GROWTH AND SEED YIELD IN HYBRID MAIZE (ARJUN) - GAJENDRA KHIDRAPURE; D. S. UPPAR; K. MARUTI; M. B. TEJAGOUDA; SHANKRAYYA (The Bioscan, 2015)
An experiment was carried out in RBD design with three replications and nine treatments. Among the treatments, significantly highest plant height (198.9 cm), number of leaves (10.30), leaf area index (2.19), chlorophyll content (54.30), dry matter accumulation (297.1 g plant-1) at harvest, cob weight (184.5 g plant-1), number of seeds (434.7 seeds cob-1), seed weight (130.7 g cob-1), shelling percentage (74.7), seed yield (58.36 q ha-1) and 100 seed weight (30.27 g) were recorded in T9 (50 % RDN through VC + 50 % RDF + ZnSO4 @10 kg ha-1 + Azospirillum @ 500 g ha-1 + PSB @ 500 g ha-1 + FYM @ 10 t ha-1). Whereas, lowest plant height (170.4 cm), number of leaves (8.40), leaf area index (1.38), chlorophyll content (43.18) and dry matter accumulation (224.0 g plant-1) at harvest, cob weight (138.9 g plant-1), number of seeds (372.4 seeds cob-1), seed weight (94.2 g cob-1), shelling percentage (62.3), seed yield (41.20 q ha-1) and 100 seed weight (24.97 g) were noticed in T2 (50 % RDN through FYM + 50 % RDF). From this study, it can be concluded that among the different treatments T9 was best to get higher seed yield in hybrid seed production of maize.